2012
DOI: 10.3748/wjg.v18.i26.3426
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hepatic arterial infusion chemotherapy in advanced hepatocellular carcinoma

Abstract: The present study demonstrates that intra-arterial FUDR chemotherapy is a safe and effective treatment for advanced HCC that is recalcitrant to other therapeutic modalities, even in patients with advanced cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Though not a significant multivariate variable, a ChildPugh score of 5 was an important factor predicting good outcome (median OS of Child class A5, A6 and B were 16, 7 and 3 mo, respectively). This result is consistent with the results of HAIC studies showing that the ChildPugh score was an independent survival factor [30,36] . Thus, HAIC using ECF could be indicated in selected patients with tumor volumes < 400 cm 3 , good hepatic reserve function, and low PIVKA-Ⅱ levels.…”
Section: Discussionsupporting
confidence: 82%
“…Though not a significant multivariate variable, a ChildPugh score of 5 was an important factor predicting good outcome (median OS of Child class A5, A6 and B were 16, 7 and 3 mo, respectively). This result is consistent with the results of HAIC studies showing that the ChildPugh score was an independent survival factor [30,36] . Thus, HAIC using ECF could be indicated in selected patients with tumor volumes < 400 cm 3 , good hepatic reserve function, and low PIVKA-Ⅱ levels.…”
Section: Discussionsupporting
confidence: 82%
“…Current treatment options for HCC, including surgical approaches, locoregional ablative techniques and interventional ablation treatments, could increase the 5-year-survival rate to 75% (vs. 30% prior to these treatments), however, <20% of HCC patients qualify for these treatments (2). Although the promising 5-year-survival rate of HCC cases has been increased due to advances in surgical techniques, nutritional support and perioperative management, long-term survival after surgical resection remains low due to the high rate of recurrence and metastasis (3,4). Novel evidence-based therapies for HCC are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that different cytotoxic agents have been used across the spectrum of different primary tumors, 5-fluoro-2'-deoxyuridine (floxuridine) has been traditionally regarded as an optimal agent for HAI. However, the experience with floxuridine in HCC is more limited 9 . In addition to fluoropyrimidine (mostly 5-fluorouracil) monotherapy 29 , the combination of 5-fluorouracil and cisplatin has been the most commonly used HAI regimen in HCC (ref.…”
Section: Discussionmentioning
confidence: 99%
“…While the experience with HAI in the West is limited 21,22 , many studies on HAI have been reported from East Asia, especially Japan. A number of prospective trials and retrospective series have reported the results of HAI in Asian patients with hepatocellular carcinoma 8,9 . The efficacy and tolerance of HAI in Asian HCC patients has also been reviewed recently [10][11][12][13]29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation